PENGARUH KUALITAS SDM DAN INFRASTUKTUR TERHADAP PERTUMBUHAN INVESTASI DI GALERI INVESTASI BEI FEBI IAIN LHOKSEUMAWE - Ismaulina, Ismaulina; Suryani, Suryani (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to explain the effect of human resources and infrastructure quality on investment growth in the Economic and Business Faculty (FEBI IDX Investment Gallery) IAIN Lhokseumawe. Data were collected using secondary data, and multiple regression was used to test the hypotheses. The results show that only investment has a significant effect on investment growth. The implications are infrastructure development have an important role to support investment and the number of potential investors in investing in the Islamic capital market.